The Effects of Host Plant Genotype and Environmental Conditions on Fungal Community Composition and Phosphorus Solubilization in Willow Short Rotation Coppice - Koczorski, Piotr; Furtado, Bliss Ursula; Gołębiewski, Marcin; Hulisz, Piotr; Baum, Christel; Weih, Martin; Hrynkiewicz, Katarzyna (Frontiers in Plant Science, 2021)
Phosphorus (P) is an essential plant nutrient. Low availability of P in soil is mainly caused by high content of Fe2O3 in the clay fraction that binds to P making it unavailable. Beneficial microbes, such as P solubilizing microorganisms can increase the available P in soil and improve plant growth and productivity. In this study, we evaluated the effects of environmental conditions (climate, soil parameters), plant genotype, and level of plant association (rhizosphere or endophytic root organism) on the abundance and diversity of phosphorus solubilizing microorganisms in a Salix production system. We hypothesized that a lower number of endophytic fungi may possess the ability to solubilize P compared to the number of rhizosphere fungi with the same ability. We also expect that the plant genotype and the experimental site with its environmental conditions will influence fungal diversity. Two Salix genotypes grown in pure and mixed cultures were investigated for their fungal microbiome community and diversity in the rhizosphere and endosphere during two growing seasons. We found that the rhizosphere fungal community was more diverse. A general dominance of Ascomycota (Dothideomycetes) and Basidiomycota (Tremellomycetes) was observed. The classes Agaricomycetes and Pezizomycetes were more frequent in the endosphere, while Tremellomycetes and Mortierellomycetes were more abundant in the rhizosphere. Plot-specific soil properties (pH, total organic carbon, and nitrogen) significantly influenced the fungal community structure. Among the culturable fungal diversities, 10 strains of phosphate solubilizing fungi (PSFs) from roots and 12 strains from rhizosphere soil were identified using selective media supplemented with di-calcium and tri-calcium phosphates. The fungal density and the number of PSF were much higher in the rhizosphere than in the endosphere. Penicillium was the dominant genus of PSF isolated from both sites; other less frequent genera of PSFs were Alternaria, Cladosporium, and Clonostachys. Overall the main factors controlling the fungal communities (endophytic vs. rhizosphere fungi) were the soil properties and level of plant association, while no significant influence of growing season was observed. Differences between Salix genotypes were observed for culturable fungal diversity, while in metagenomic data analysis, only the class Dothideomycetes showed a significant effect from the plant genotype.